Aerosol absorption over the Aegean Sea under northern summer winds. (15th June 2020) - Methymaki, Georgia; Bossioli, Elissavet; Kalogiros, John; Kouvarakis, Giorgos; Mihalopoulos, Nikolaos; Nenes, Athanasios; Tombrou, Maria
Abstract: In this modelling study, the absorption influence on radiation, apart from scattering, is studied above the Aegean Sea (Eastern Mediterranean) under a typical warm 13-day period with northern winds, transporting polluted air masses. The simulated (WRF-Chem) forcing caused by the total absorption is estimated along with black carbon (BC), dust, and sea salt contributions, 1.3, 1.2, 0.1 and nearly zero W m −2, accordingly. As dust and sea salt influence is negligible, the main focus is on BC. BC absorption reduces downward shortwave irradiance reaching the ground by up to 5.2 W m −2 and the upward part by up to 1.7 W m −2 . The downward and the upward longwave irradiances are augmented by up to 2.3 and 1.2 W m −2, accordingly. Even though the cloud formation is not favoured during the study period, BC absorption reduces overall the cloud water mixing ratio by 10% (semi-direct effect). However, during specific days and over limited cloudy areas, the semi-direct effect reduces low level clouds up to 20% while in case of higher clouds the reduction reaches up to 29%. In order to examine the physical mechanisms below semi-direct effect, all modelled heating rates are analysed. Radiation direct absorption increases the air temperature with a rate up to 0.2 K day −1, with an exception inside the surface layer, where unexpectedly longwave cooling prevails. The heating of the surface layer is mainly attributed to the advection process, as more heated air masses are transported over the Aegean Sea. Highlights: The forcing of BC, dust, and sea salt absorption under Etesians is estimated at 1.2, 0.1 and nearly zero W m −2, accordingly. BC absorption reduces the SW↓ by 5.5 W m -2 near the surface and augments the LW↑ by 0.3 W m -2 at the TOA. BC absorption reduces the cloud water mixing ratio on average by 10% (semi-direct effect). BC absorption influences all physical and dynamical heating processes producing heating rates up to 0.2 K day −1 . The mean daily temperature increases by up to 0.8 K near the surface.